ANALISIS MODEL MODEL KEBANGKRUTAN PADA PERUSAHAAN ASURANSI DI INDONESIA - Octaviani, Ermi; Situmeang, Chandra (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
Research on various models of financial distress analysis has been developed to predict the beginning of corporate bankruptcy, such as the Springate model, Altman Z-Score, Grover, and others. Each type of company provides varying accuracy in each analysis model based on variations in the findings of previous research investigations. This research aims to analyze whether the Springate, Altman Z"-Score, and Grover models can be used in predicting corporate financial distress. The research was conducted on insurance companies at the Financial Services Authority in 2021. The sampling technique used purposive sampling techniques. A research sample of 76 companies that met the sampling criteria was obtained, and a total research population of 127 companies was used. This research is quantitative research where the analytical tool used is a logistic regression test with SPSS version 25. The results of this study show that the springate model can be used in predicting financial distress of insurance companies with a significance value of 0.001 < 0.05, H1 received. The Altman Z-score model could not predict the financial distress of insurance companies with a value of 0.298 > 0.05 H2 rejected. Grover's model can be used to predict insurance companies' financial distress with significance values of 0.004 < 0.05 H3 received.